ALPHA PSYCHIATRY 2022
DOI: 10.5152/alphapsychiatry.2022.21783
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Consequences of COVID-19 Pandemic: A Synthetic Review from a Global Perspective

Abstract: Some research suggests that distress, secondary to isolation and fear following COVID-19 infection, can negatively affect the long-term more than the COVID-19 infection itself. This narrative review aims to provide a global view on the neuropsychiatric consequences of COVID-19 that can be ascribed to several factors, ranging from the direct effect of infection, to the body’s responses against the infection, or to the psychological sequelae of social isolation, unemployment, and fear for one’s health and liveli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…The emergence of COVID-19 has become a global pandemic in March 2020 1. The negative impact of the pandemic on individuals is multifaceted, affecting aspects such as daily life, physical health, mental health, economics and society 2. Undoubtedly, the pandemic has heightened significant economic and social challenges on a global scale.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The emergence of COVID-19 has become a global pandemic in March 2020 1. The negative impact of the pandemic on individuals is multifaceted, affecting aspects such as daily life, physical health, mental health, economics and society 2. Undoubtedly, the pandemic has heightened significant economic and social challenges on a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…During the initial phase of widespread epidemics, it is often observed that a larger-than-expected number of individuals experience mental health issues. There is evidence suggesting that pandemics have a significant impact on mental disorders 2 4. Pandemics have the potential to trigger new psychiatric symptoms in individuals who have no history of such disorders, exacerbate existing mental health conditions and even lead to mental health challenges among the caregivers of those affected by SARS-CoV-2 infection 5.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations